Memorial acadêmico: trajetória escolar, acadêmica e profissional de uma eterna aprendiz - Marques, Belmara de Macedo (Brasil, 2024)
This descriptive academic memorial aims to report my school, academic and professional trajectory and, by traveling these tortuous paths of memory, be able to discuss challenges encountered along this long journey. In an academic memorial format, this final course work also explains issues relevant to teaching and the immeasurable contribution of Pedagogy to the historical-social construction of much more inclusive classrooms. The work is structured into an introduction, trajectory in Elementary School – Early Years and trajectory in Elementary School – Final Years and trajectory in High School. The author seeks to reflect on social conflicts experienced during her schooling process, articulating these (re)lived memories with social processes that reveal themselves as true obstacles to be overcome in the stages of Basic Education, about which, it is concluded that, Without the development of inclusive pedagogical practices, problems such as school dropout are more than present. Subsequently, this work seeks to discuss social issues that can continue during higher education, such as the obstacles and frustrations faced when studying Pedagogy at the Federal University of Amazonas. This problematization exercise is accompanied by theoretical-methodological perspectives learned at different moments during graduation, including their experiences, internship trajectory, teaching experience, approval in competitions and all the motivation that involves the act of studying Pedagogy.